2011
DOI: 10.1007/s12678-011-0071-0
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Supported Silver as Cathode Electrocatalyst for Alkaline Polymer Electrolyte Membrane Fuel Cells

Abstract: Carbon-supported silver in varying percentage viz. 40%, 60%, and 80% (Ag/C) is prepared by sodium citrate protecting method. The structure, dispersion, electrochemical characterization, and surface area and oxygen reduction reaction pathway of Ag/C are determined by XRD, TEM, CV, and LSV, respectively. The catalyst is evaluated for its electrocatalytic activity towards oxygen reduction reaction (ORR) in alkaline polymer electrolyte membrane fuel cells (APEMFCs); 60% Ag/C gives higher performance than 40%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 29 publications
5
49
0
3
Order By: Relevance
“…Preparation of Ag/TiO 2 and Ag/C catalysts The previously reported citrate-protecting method [28,32] was used to obtain the different Ag/TiO 2 catalysts. In contrast to previous reports, the support materials used here (TiO 2 or carbon black) were first mixed with AgNO 3 (40 mm; Sigma-Aldrich) aqueous solution to allow the better adsorption of Ag + on the support.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of Ag/TiO 2 and Ag/C catalysts The previously reported citrate-protecting method [28,32] was used to obtain the different Ag/TiO 2 catalysts. In contrast to previous reports, the support materials used here (TiO 2 or carbon black) were first mixed with AgNO 3 (40 mm; Sigma-Aldrich) aqueous solution to allow the better adsorption of Ag + on the support.…”
Section: Methodsmentioning
confidence: 99%
“…Similar trends and explanations have been reported for other supported catalysts, for example, for Ag supported on carbon black in fuel-cell applications. [28] One of the main advantages of the Ag/TiO 2 catalysts studied in this paper is their low mass fraction of Ag, which reduces the amount of precious metal needed. The performance per mass Ag (i.e., the mass activity) for all catalysts used in this study is compared in Figure 2 c. For example, the mass activity of 5 wt % Ag/TiO 2 was 20-fold higher than that of the commercial AgNP catalyst and much higher than the mass activity of N-based Ag catalysts (e.g., Ag pyrazole, AgPz), which we reported previously with a high mass activity of 1600 mA mg Ag À1 cm À2 at À1.7 V vs. Ag/AgCl.…”
Section: à2mentioning
confidence: 99%
“…Various catalysts have been investigated to improve the kinetics and the proportion of four-electron pathway during the ORR, such as noble metals [5][6][7][8][9][10][11][12][13], metal oxides [14][15][16] and carbon based nanomaterials [17][18][19]. Among these catalytic materials studied before, the Ag or Ag/C is supposed to be a competitive material to replace the Pt due to its relative low cost and high activity toward the ORR in alkaline medium [20][21][22][23][24][25][26]. However, the performances of Ag based catalysts are affected by the agglomeration of the Ag nanoparticles and the electrochemical corrosion of the catalyst supports, which needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, in another report from F. H. B. Lima et al, a 2.3-electron pathway of ORR in alkaline media catalyzed by 20%Ag/C was found [11]. Furthermore, Subbiah Maheswari et al and Junsong Guo et al found that 60%Ag/C had the highest ORR activity in alkaline media [12,13]. Despite of the controversies, the reported results suggest that Ag has high potential as an alternative low-cost ORR catalyst.…”
Section: Introductionmentioning
confidence: 92%